Study of Hydrological Parameter with Respect to DEM Using GIS & RS in Nelliampathy Hill, Kerala - Subramani, T; A.Niasi, K (International Journal of Engineering and Technology, 2018)
Digital elevation models (DEMs) represent the total topography, surface flow is one of the more important data sources for deriving variables used by numerous hydrologic models. A lot of research has been directed to address vulnerability related with error in digital height models (DEMs) and the spread of blunder to determined terrain parameters. This audit unites a discourse of research in major topical regions identified with DEM vulnerability that influence the utilization of DEMs for hydrologic applications. The work is to give some understanding into the characterization of elevation data quality and the relationship amongst topography and water assets models. A key characteristic of circulated displaying is the spatially factor portrayal of the watershed as far as topography, vegetative, or land use/cover, soils and impenetrable territories and the subordinate model parameters that represent the hydrologic procedures of infiltration, evapotranspiration, and runoff. In our study, application of DEM and deriving hydrological parameters using remote sensing and GIS technology at Nelliampathy hill, Kerala.